Trust-oriented composite service selection with QoS constraints - LI, Lei (Institutional Knowledge at Singapore Management University, 2010)
In Service-Oriented Computing (SOC) environments, service clients interact with service providers for consuming services. From the viewpoint of service clients, the trust level of a service or a service provider is a critical factor to consider in service selection, particularlywhen a client is looking for a service from a large set of services or service providers. However, a invoked service may be composed of other services. The complex invocations in composite services greatly increase the complexity of trust-oriented service selection. In this paper, we propose novel approaches for composite service representation, trust evaluation and trust-oriented com-posite service selection (with QoS constraints). Our experimental results illustrate that compared with the existing approaches our proposed trust-oriented (QoS constrained) composite serviceselection algorithms are realistic and enjoy better efficiency.